(untitled) (Ozone Therapy Global Journal, 2022)
Context: Currently, there is no effective antiviral therapy recommended for Chronic-Epstein- Barr-Virus Syndrome or for Post-Epstein-Bar-Virus Fatigue Syndrome Aims: To assess the efficacity of ozonised saline solution(O3SS) used as a complementary therapy in adults who suffer from -Epstein-Bar-Virus Fatigue Syndrome or from Chronic-Epstein- Barr-Virus Syndrome Methods: Ten adult patients with chronic fatigue symptoms since their EBV-infection (>6 months) were included in this observational case study. Prior to initiating, and two weeks after treatment the Fatigue Severity Scale and lab values to monitor the changes in EBV-VAC-IgG, EBV-VAC-NA, EBV-EA, EBV IgM, Th1 , Th2, CD4 and CD8 were obtained. Patients were treated with O3SS, six sessions at a rate of three sessions a week then four sessions at a rate of two sessions a week (ten sessions in total). No control group was included. Secondary endpoints assessed included the fatigue score of participants and laboratory examinations. Results: O3SS treatment demonstrated a significant (p<0.01) tendency to improve Fatigue Severity Scale and improve laboratory examination results. No side effects were noted during the duration of the study. Conclusion It would be interesting to have further investigation to know which patients belong to the 20% EBV-EA positive patients who are healthy and more investigation is needed to learn to evaluate the subjective improvements in the lab values, probably by EBV PCR testing or examining the frequencies of CD8+ T-cells specific for EBV latent and Lytic Ags in healthy virus carriers could be interesting.